Virus and microbial loop dynamics over an annual cycle in three contrasting Antarctic lakes - Madan, NJ; Marshall, WA; Laybourn-Parry, J (2005)
1. Viral and microbial loop dynamics were investigated over an annual cycle in three contrasting saline Antarctic lakes – Highway Lake (salinity 4&), Pendant Lake (salinity 19&) and Ace Lake, a meromictic system (with a mixolimnion salinity of 18&) in order to assess the importance of viruses in extreme, microbially dominated systems. 2. Virus like particles (VLP) showed no clear seasonal pattern, with high concentrations occurring in both winter and summer (range 0.89 · 107 ± 0.038 to 12.017 · 107 ± 1.28 mL)1). VLP abundances reflected lake productivity based on chlorophyll a concentrations. Bacterial abundances and biomass did not correlate with VLP numbers except in Pendant Lake, the most productive of the three lakes studied. 3. Pendant Lake supported the highest bacterial biomass (range Highway: 18.44 ± 1.35 to 59.43 ± 2.80 ng C mL)1; Ace: 14.42 ± 2.69 to 68.39 ± 2.95 ng C mL)1; Pendant: 31.36 ± 3.94 to 115.95 ± 4.49 ng C mL)1) so that virus to bacteria ratios (VBR) (range 30.48 ± 7.96 to 96.67 ± 8.21) were higher in Ace Lake (range 30.58 ± 3.98 to 80.037 ± 1.60) and Highway Lake (range 18.63 ± 3.12 to 126.74 ± 6.50). 4. Negative correlations occurred between VLP and cryptophytes (dominant phototrophic nanoflagellates), suggesting that they were not hosts to lytic viruses. Among the other protists only the heterotrophic nanoflagellates of Highway Lake (dominated by the marine choanoflagellate Diaphanoeca grandis) showed a positive correlation with VLP. 5. The VLP was negatively correlated with photosynthetically active radiation (PAR) and temperature, both of which increased with ice thinning and breakout, increasing viral decay. In winter VLP probably persisted in cold, dark water. 6. High VLP concentrations and high VBR (values at the upper end of those reported for marine and lacustrine systems) indicated that viruses, most of which were probably bacteriophage, are a major element within the microbial communities in extreme, saline lakes.